#TITLE_ALTERNATIVE# - HANIF ABIDIN (Nim : 12308027), MUHAMMAD
Seismic Data Processing aims to create a seismic section which reflect true-condition subsurface image. Besides conventional method (using CMP stack), we can use another method which is called Common Reflection Surface method. Unlike CMP stack which only sums traces along offset, CRS stack sums traces along offsets and midpoints around targeted midpoint. Because more data is used, CRS stack create section with higher signal to noise ratio compared to conventional method. CRS method can also create gather data using process which is called Partial CRS Stack. This gather can be used as an input for Prestack Depth Migration Before migration we create interval velocity model using Coherency Inversion. Coherency Inversion done twice using CMP gather and CRS gather as a data input so we created two different velocity model. First model created using CMP gather will be used as an input data for PSDM using CMP gather, and the second velocity model created using CRS gather will be used as an input data for PSDM using CRS gather. PSDM using CRS gather and CRS velocity create a section with higher signal to noise ratio and higher continuity along reflectors. Depth Migrated gather analysis and reflector geometry in depth migrated section analysis gives us a conclusion that velocity model created using Coherency Inversion with input CRS gather is more acurate.